2023
DOI: 10.3390/healthcare11131955
|View full text |Cite
|
Sign up to set email alerts
|

Access to Healthcare and Health Literacy in Croatia: Empirical Investigation

Abstract: Health literacy is related to different health-related outcomes. However, the nature of the relationship between health literacy and health outcomes is not well understood. One pathway may lead from health literacy to health outcomes by means of access to healthcare. The goal of the current study is to explore the association between health literacy and the particular measure of access to healthcare—unmet medical need—for the first time in Croatia and, to the best of our knowledge, for the first time in the EU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
(63 reference statements)
0
2
0
Order By: Relevance
“…However, approximately one in five women in this study reported not knowing how to access the health services they needed, which may include GPs and other primary healthcare providers. Similarly, studies have reported that people with unmet healthcare needs are more likely to have poor health literacy [37]. This suggests that easy-to-understand information on how to access health services is essential.…”
Section: Discussionmentioning
confidence: 99%
“…However, approximately one in five women in this study reported not knowing how to access the health services they needed, which may include GPs and other primary healthcare providers. Similarly, studies have reported that people with unmet healthcare needs are more likely to have poor health literacy [37]. This suggests that easy-to-understand information on how to access health services is essential.…”
Section: Discussionmentioning
confidence: 99%
“…Health literacy is defined as the degree to which individuals can attain, understand, and use health information as a basis for making correct health decisions and following treatment-related advice [23,24]. We expect that as individuals become more health literate, their propensity to consume take-out food diminishes.…”
Section: Health Literacymentioning
confidence: 99%